The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/bjdm-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

The role of parental education in the dental health behavior of Turkish secondary school children

Abstract: SummaryBackground/Aim: Parents are usually the major factor influencing children’s development of routine oral health behavior. A higher education level of the parents is generally associated with having a more positive influence on their children’s health habits and motivation to maintain healthy dentition. From this perspective, the aim of the present study was to investigate the frequency of certain habits influencing dental health, such as toothbrushing, regular visits to the dentist, and changing toothbru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
5
0
4
Order By: Relevance
“…It has also been reported that fathers’ greater frequency of toothbrushing is associated with children’s lower scores on the Decayed, Missing due to caries, and Filled Teeth (DMFT) index [39]. However, this finding has not been consistent across previous studies, as Karaaslan et al found that while parental educational level was associated with children’s frequency of dentist visits, there was no significant association between parental educational level and child toothbrushing frequency [40]. This suggests that further research must be done on this topic to clarify the relationship between parental education and children’s oral health and toothbrushing habits.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been reported that fathers’ greater frequency of toothbrushing is associated with children’s lower scores on the Decayed, Missing due to caries, and Filled Teeth (DMFT) index [39]. However, this finding has not been consistent across previous studies, as Karaaslan et al found that while parental educational level was associated with children’s frequency of dentist visits, there was no significant association between parental educational level and child toothbrushing frequency [40]. This suggests that further research must be done on this topic to clarify the relationship between parental education and children’s oral health and toothbrushing habits.…”
Section: Discussionmentioning
confidence: 98%
“…These results differ from previous studies, which reported that parents with higher socioeconomic status tend to be more motivated in seeking dental and oral health care for their children. 16,39,40 This contrast may be because parents from middle to lower socioeconomic status are also highly motivated to obtain knowledge and information about dental and oral health through the internet or other easily accessible media. In contrast, parents from middle to lower socioeconomic status are not too concerned with dental and oral health, usually they are only concerned with the general health of their child.…”
Section: Discussionmentioning
confidence: 99%
“…48 Inisiatif ibu merupakan hal yang menentukan pemeliharaan kebersihan gigi dan mulut anak, utamanya dalam upaya pencegahan dan promotif terhadap masalah kesehatan gigi dan mulut. 50 Perilaku ibu tampak tetap menjadi variabel independen dalam promosi kebersihan gigi dan mulut bagi usia remaja yang proses pembentukan kesadaran dirinya sudah hampir selesai. 48 Ibu merupakan model sosial yang penting dalam pembentukan perilaku kesehatan gigi dan mulut pada masa remaja karena perilaku tersebut akan terbawa hingga dewasa.…”
Section: Pembahasanunclassified